Karang Boma: Musical Composition Based on History, Painting and Kawi Dalang Art Creativity Theory (Jurnal Seni Musik, 2022)
The emergence of experimental music is marked by the presence of the figure of John Cage in the 19th century which in music history is often referred to as the period of Modern Music. John Cage is a composer who is full of controversy because his works are experimental and out of the rules contained in music in previous eras such as baroque, classical and romantic eras. One of his most famous works is “4.33” this work is a piano piece complete with sheet music and performed live but the pianist does not play a single note, and only opens and closes the piano according to the direction of the sheet music. The presence of Cage's figure has inspired many people, especially myself. Inspired by experimental music composers, I decided to create a piece of music that combines music with Balinese painting called Karang Boma. This work will be realized in the form of sheet music and midi art. The method of creation used by the author in Karang Boma's musical works refers to the Panducita Subagaprana Theory, this theory is divided into four namely: Pandulame (imajination), Adicita (Idea), Subagalango (Art Compotition), and Pranayuga (External Trend/Tendency).